2022
DOI: 10.52142/omujecm.39.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the COVID-19 pandemic on fracture distribution: Epidemiological data from a tertiary trauma center in Turkey

Abstract: Redefinition of our social life for COVID-19, with social distance, prohibition of entering and exiting cities, closure of social areas and curfews effects every aspect of our lives, from psychological to physical. The aim of this study was to evaluate the injury mechanisms, fracture frequencies and priority treatment preferences in a tertiary trauma center from Turkey during the COVID-19 pandemic, both in adult and pediatric populations, and to compare them with pre-COVID-19 period. In this single-centered st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is a logical assumption that, with increased indoor time, common reasons for fractures such as traffic accidents will decline whereas minor fractures due to domestic accidents will increase. [ 23 ] These results can be explained by the changes in people’s daily habits, social activities, and working patterns due to the curfews.…”
Section: Discussionmentioning
confidence: 99%
“…It is a logical assumption that, with increased indoor time, common reasons for fractures such as traffic accidents will decline whereas minor fractures due to domestic accidents will increase. [ 23 ] These results can be explained by the changes in people’s daily habits, social activities, and working patterns due to the curfews.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Curry et al (2014) reported that 50% of orthopaedic patients used the internet for health problems, and 26% did preliminary research before visiting a doctor. Moreover, during the pandemic, extraordinary measures have been taken all over the world, and citizens have had to spend a long time in their homes (Gencer & Doğan, 2022; Yavuz et al, 2021). This situation has changed habits and promoted the use of the internet and social media.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the easier access to information triggers patients' tendency to self‐medicate or to research their diseases before seeing a physician. Especially since March 2020, after the outbreak of the COVID‐19 pandemic, the rate of patients doing preliminary research and self‐medicating by resorting to the internet have increased significantly, considering that people got used to living for a long time due to the circumstances of restrictions such as the curfews (Gencer & Doğan, 2022; Gencer, Çulcu, & Doğan, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one-fourth of childhood injuries involve the elbow area. 16 Although most of them are supracondylar fractures, the pulled elbow should be kept in mind, especially in children under six years of age with a history of sudden traction. 1,2,5,6 As mentioned before, the prevailing view in the literature is that the diagnosis of the pulled elbow should be made clinically, and unnecessary radiation should be avoided.…”
Section: Discussionmentioning
confidence: 99%